Cultural Constellations and Childhood Identities: On Greek Gods, Cartoon Heroes, and the Social Lives of Schoolchildren - Dyson, Anne Haas (Harvard educational review, 1996)
Describes children's participating in dramatic play activities that are teacher or peer governed. Illustrates children's use of cultural symbols as material for story construction and social affiliation. Argues for a literacy curriculum in which cultural symbols are open to critical examination. (Author/SK)